Development of the ATM Method (Observe, Imitate, and Modify) in Audio Visual Integrated Poetry Reading Skills - Winda Wulandari; Edhy Rustan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study aims to analyze needs, determine the design and test the validity of teaching materials using the ATM method in audio-visual integrated poetry reading skills in class IV SDN 069 Limbong. The research was developed using the Research and Development (R&D) method and refers to the ADDIE model, which consists of five stages. However, this study was only carried out in up to 3 stages: analysis, design and development. This research was conducted at SDN 069 Limbong, located in Limbong Village, Rongkong District, North Luwu Regency. The instruments used were teacher interviews and student questionnaires. The analysis using teacher interviews shows that the teacher only uses the lecture method in the learning process, so there is no student interest in learning. The results of the student questionnaire show that students prefer teaching materials and media such as videos. The ATM method is structured and designed considering basic competencies and learning objectives. Teaching materials for the integrated audio-visual ATM method were assessed by three experts, including language and material experts, who obtained a percentage of 92.5% with a very valid category, design experts obtained a rate of 95% with a very valid category, and application experts obtained 93.7% with a very valid category.